2018
DOI: 10.3892/mmr.2018.9413
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid therapy in IgA nephropathy with minimal proteinuria and high renal pathological score: A single‑center cohort study

Abstract: Currently, there is no clear evidence that advocates the widespread use of corticosteroids for the treatment of immunoglobulin A nephropathy (IgAN) with minimal proteinuria (<1 g/day). The recent Kidney Disease: Improving Global Outcomes Clinical Practice Guideline recommends supportive corticosteroid treatment. In the present study, 45 IgAN patients with high renal pathological scores and minimal proteinuria were enrolled. The patients were randomly divided into two groups. The treatment group received methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Interestingly, more recently, Novak and coworkers (29) observed that STAT3 was differentially activated by IL-6 in IgA1-secreting cells from patients with IgA nephropathy compared with those from healthy controls, and inhibition of STAT3 signaling reduces IgA1 autoantigen production in IgA nephropathy. We observed increased STAT3 mRNA expression in PBMCs from IgA nephropathy, which can be also observed in another independent study (42,43). STAT3 is a central member of the JAK/STAT signaling cascade and has long been recognized for its increased transcriptional activity in cancers and autoimmune disorders, but it has only recently been in the spotlight for its role in the progression of kidney disease (44) GABBR1…”
Section: Stat3supporting
confidence: 75%
“…Interestingly, more recently, Novak and coworkers (29) observed that STAT3 was differentially activated by IL-6 in IgA1-secreting cells from patients with IgA nephropathy compared with those from healthy controls, and inhibition of STAT3 signaling reduces IgA1 autoantigen production in IgA nephropathy. We observed increased STAT3 mRNA expression in PBMCs from IgA nephropathy, which can be also observed in another independent study (42,43). STAT3 is a central member of the JAK/STAT signaling cascade and has long been recognized for its increased transcriptional activity in cancers and autoimmune disorders, but it has only recently been in the spotlight for its role in the progression of kidney disease (44) GABBR1…”
Section: Stat3supporting
confidence: 75%
“…A total of 10,622 related studies were retrieved from various databases, and after screening, 11 RCTs were finally included (10,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) in this meta-analysis. The literature screening process is shown in Figure 1.…”
Section: Literature Retrieval Resultsmentioning
confidence: 99%
“…A previous study indicated that the p53 signaling pathway is associated with the progression of IgAN and associated renal outcomes [ 38 ]. An earlier study reported that the dysregulation of cytokine levels is associated with the activation of the JAK-STAT signaling pathway, and the latter plays a role in IgAN pathogenesis and progression [ 39 ].…”
Section: Discussionmentioning
confidence: 99%